Latissimus muscle sparing approach to subscapular rib fracture plating. (December 2019) - Makey, Ian A.; Jacob, Samuel; El-Sayed Ahmed, Magdy M.; Pham, Si; Landolfo, Kevin; Thomas, Mathew
Abstract: Surgical stabilization of fractured ribs has been shown to improve trauma related outcomes, however the procedure itself can be a source of morbidity. This report details two cases of latissimus dorsi muscle sparing sub-scapular multi-rib fracture plating. We combined several techniques to make this possible. The first technique was use of a vertical skin incision along the anterior border of the latissimus muscle. The second was the use of a mammary retractor to provide adequate and sustained retraction of the latissimus and scapula. The third was utilization of a right angle screwdriver to allow placement of the posterior screws. Sparing the latissimus muscle for sub-scapular fractures is possible but requires planning and extra equipment to perform. Minimizing rib fixation related morbidity makes it a more appealing treatment.